Pregnancy outcome in elderly primigravida - Pradhan, Kumudini; Baru, Lina; Dharua, Ashish (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Incidence of elderly primigravida has increased now days, due to rising education level, effective means of birth control and high carrier goals. The women who conceived in advanced age more than 35 years for first time is defined as elderly primigravida. Indian standard is fixed at more than 30 years by Dutta 2013. These women are high risk for maternal and foetal complication and outcome. The study was done to assess pregnancy outcome in elderly primigravida. Methods: This is a prospective hospital-based study done from October 2016 to November 2018. Women of reproductive age group with first pregnancy admitted to department of obstetrics and gynaecology, Veer Surendra Sai Institute of Medical Science and Research, Burla were taken after exclusion criteria. Results: The incidence of elderly primigravida was 2.51%. But majority (84.76%) though married early, conceived late. Most of them are belongs to high socioeconomic group (62.86%). Anaemia was commonest complication (28.57%), fibroid in 5.71% cases. Pre-eclampsia (18.09%), eclampsia (3.81%), IUGR (12.38%) and twin pregnancies (5.72%) were seen more frequently than young primigravida. 55.24% were developed complications during labour like foetal distress (33.33%), PPH (3.81%) and retained placenta (2.86%). Gestational diabetes mellitus in (0.95%), caesarean section rate 29.52%, normal delivery 51.42%, and congenital anomaly 8.15%. Conclusions: Elderly primigravida are high-risk for several complications like spontaneous abortion, preterm labour, prolonged labour, foetal distress, high caesarean rate, PPH, congenital anomaly and increased incidence of perinatal mortality. Majority of this patients properly supervised are capable of safe and successful pregnancies ending in healthy mother and healthy baby.